Investigation of internal action to enhance structural stability and electrochemical performance of K+/Mg2+ co-doped cathodes in high voltage environments utilizing dual coordination - Xuantian Feng; Minjie Hou; Bowen Xu; Yiyong Zhang; Da Zhang; Yun Zeng; Yong Lei; Feng Liang (Materials Reports: Energy)
Sodium-ion batteries (SIBs) are emerging as a promising alternative for large-scale energy storage, particularly in grid applications. Within the array of potential cathode materials, Fe/Mn-based layered oxides are notable for their advantageous theoretical specific capacity, economic viability, and environmental sustainability. Nevertheless, the practical application of Fe/Mn-based layered oxides is constrained by their suboptimal cycle performance and rate capability during actual charging and discharging. Ion doping is an effective approach for addressing the aforementioned issues. In this context, we have successfully developed a novel K+ and Mg2+ co-doped P2-Na0.7Fe0.5Mn0.5O2 cathode to address these challenges. By doping with 0.05 K+ and 0.2 Mg2+, the cathode demonstrated excellent cycling stability, retaining 95% of its capacity after 50 cycles at 0.2C, whereas the undoped material retained only 59.7%. Even within a wider voltage range, the co-doped cathode retained 88% of its capacity after 100 cycles at 1C. This work integrated Mg2+ to activate oxygen redox reactions in Fe/Mn-based layered cathodes, thereby promoting a reversible hybrid redox process involving both anions and cations. Building on the Mg doping, larger K+ ions were introduced into the edge-sharing Na+ sites, enhancing the material's cyclic stability and expanding the interplanar distance. The significant improvement of Na+ diffusion coefficient by K+/Mg2+ co-doping has been further confirmed via the galvanostatic intermittent titration technique (GITT). The study emphasizes the importance of co-doping with different coordination environments in future material design, aiming to achieve high operating voltage and energy density.